Medicinal plants used in the treatment of diseases of the respiratory system by the Andean community of Pampas, Tayacaja, Huancavelica - Saldaña-Chafloque, Charles Frank (2022)
Objective: to identify the medicinal plants used in the therapy of respiratory system disorders by the Andean community of Pampas, Tayacaja, Huancavelica. Methodology: Semi-structured, random interviews were used, considering exclusion and inclusion criteria for the study sample of 370 inhabitants. Results: The ethnomedicinal use of 13 species and 10 families of medicinal plants used for the therapy of respiratory system conditions such as influenza, bronchitis, asthma, cold, cough, laryngitis, pharyngitis, bronchitis, tonsillitis, pneumonia is reported. Conclusions: The Andean inhabitant of the Pampas reports the families Anacardiaceae, Asteraceae, Boraginaceae, Geraniaceae, Lamiaceae, Myrtaceae, Nyctaginaceae, Onagraceae, Piperaceae and Plantaginaceae and 13 species; used in the therapy of affections of the respiratory system; where the widely used species is Eucalyptus globulus (69%).